2016
DOI: 10.1210/jc.2015-4106
|View full text |Cite
|
Sign up to set email alerts
|

Low Free Testosterone Is Associated with Hypogonadal Signs and Symptoms in Men with Normal Total Testosterone

Abstract: Low cFT, even in the presence of normal TT, is associated with androgen deficiency-related symptoms. Normal cFT, despite low TT, is not associated with cognate symptoms; therefore, cFT levels should be assessed in men with suspected hypogonadal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 45 publications
10
90
0
Order By: Relevance
“…More recently, the CHAMP study showed a decline of serum total T around 2% per year 81 ( Table 3). The EMAS results have confirmed, in the last years, the data concerning the progressive decline in aging men of serum total T, free T, and E 2 82 , as well as those concerning the rise of SHBG with aging 83 (Table 3). The CHAMP recently replicated these results except for a surprising increase of E 2 81 (Table 3).…”
Section: Risk Increasesupporting
confidence: 74%
See 2 more Smart Citations
“…More recently, the CHAMP study showed a decline of serum total T around 2% per year 81 ( Table 3). The EMAS results have confirmed, in the last years, the data concerning the progressive decline in aging men of serum total T, free T, and E 2 82 , as well as those concerning the rise of SHBG with aging 83 (Table 3). The CHAMP recently replicated these results except for a surprising increase of E 2 81 (Table 3).…”
Section: Risk Increasesupporting
confidence: 74%
“…4,8,82,83,89,90 However, according to a more recent analysis, total serum T levels seem to be quite stable until the age of 70 years, after that there would be a progressive, significant decline, while the bioavailable serum T seems to decline more linearly with aging. 79 In line with other studies, 3,8,89,90 in the Tromsø study the investigation of hormonal changes with aging resulted in the finding of lower serum T levels and higher gonadotropins levels in older men 60 (Table 3), even though the measurement of gonadotropins in aging men is scarcely helpful in predicting the future development of hypogonadism 91 (Table 3).…”
Section: Consequences Of Hormonal Changes Related To Male Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…• A TT level <8 nmol/L or a free testosterone (FT) level <0.180 nmol/L usually requires therapy 4,6,21 • A TT level >12 nmol/L or a FT >0.225 nmol/L does not require therapy 4,6,21 • Levels between 8-12 nmol/L may require a trial of testosterone therapy (minimum six months), based on symptoms 4,6,21 • A FT level <0.225 nmol/L provides supportive evidence for TT 22 Furthermore:…”
Section: Box 2 Thresholds For Testosterone Therapy (Tt)mentioning
confidence: 99%
“…Furthermore, longitudinal studies have clearly documented the decline in testosterone with aging [1,52]. Testosterone levels decrease steadily and continuously during aging, resulting in late-onset hypogonadism (LOH).…”
Section: Androgen-deprivation Therapy Late-onset Hypogonadism (Loh) mentioning
confidence: 99%